Transcriptional landscape and chromatin accessibility reveal key regulators for liver regenerative initiation and organoid formation - Jiabei Lian; Yachun An; Wenjing Wei; Yao Lu; Xiyu Zhang; Gongping Sun; Haiyang Guo; Longjin Xu; Xuena Chen; Huili Hu (Cell Reports)
Summary: Liver regeneration is a well-organized and phase-restricted process that involves chromatin remodeling and transcriptional alterations. However, the specific transcription factors (TFs) that act as key “switches” to initiate hepatocyte regeneration and organoid formation remain unclear. Comprehensive integration of RNA sequencing and ATAC sequencing reveals that ATF3 representing “Initiation_on” TF and ONECUT2 representing “Initiation_off” TF transiently modulate the occupancy of target promoters to license liver cells for regeneration. Knockdown of Atf3 or overexpression of Onecut2 not only reduces organoid formation but also delays tissue-damage repair after PHx or CCl4 treatment. Mechanistically, we demonstrate that ATF3 binds to the promoter of Slc7a5 to activate mTOR signals while the Hmgcs1 promoter loses ONECUT2 binding to facilitate regenerative initiation. The results identify the mechanism for initiating regeneration and reveal the remodeling of transcriptional landscapes and chromatin accessibility, thereby providing potential therapeutic targets for liver diseases with regenerative defects.